Constitution (Frigate) notebook - Constitution (Frigate)
Notebook (96 pages) of the frigate Constitution.
Microfilm edition available
Microfilm edition produced from original in Manuscript Division.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Ship's papers -- 19th century